The first ongoing pregnancy following comprehensive aneuploidy assessment using a combined blastocenetesis, cell free DNA and trophectoderm biopsy strategy - Ben-Nagi, J; Odia, R; Viñals Gonzalez, X; Heath, C; Babariya, D; SenGupta, S; Serhal, P; Wells, D (Avicenna Research Institute, 2019)
Background: The exact origin of cell-free DNA found in spent culture media or blastocoel fluid is currently unknown but with the potential to become an improved source of DNA for chromosomal analysis than trophectoderm biopsy samples, it provides a superior representation of the fetal genetic status. However, the genetic material contained within the blastocoel cavity may be more reliable to assessment of embryo euploidy in a clinical context than trophectoderm of cell-free DNA.